Interlinking Behaviour, Technology, and Roles in Women Seed Producer Groups of Bangladesh - Nayak, Swati; Habib, Muhammad Ashraful; Mohapatra, Subhasmita; Islam, Saidul; Hossain, Sk Mosharaf (International Rice Research Institute, 2025)
This case study explored how organizational behavior, the use of digital technology, and value chain roles of members collectively influenced the success of women-led rice seed producer groups (WLRSPGs) in Bangladesh. Analyzing five unique groups across three geographical divisions of the country, the study analyzed leadership styles, group cohesion, communication patterns, adaptability, digital tool use, and functional roles. The case study examined the proposition that groups exhibiting transformational leadership, along with high cohesion and effective communication, significant adoption of digital tools, and broader functional roles tend to achieve greater market reach, enhanced operational efficiency, and stronger future readiness. Findings suggested that while transformational leadership and technology adoption fostered innovation and resilience, financial success in rice seed entrepreneurship was primarily driven by producing certified seeds for regional and national markets, with greater control over the value chain by the members. Additionally, seed producer-only groups exhibited higher rice seed production, which correlated with higher seed income; in contrast, federated groups relied on non-seed income and diversification. The research highlights the importance of product and market decisions and greater roles in the value chain alongside skill development and digital literacy in empowering women in agriculture, providing valuable insights for policymakers and development practitioners.